MENINGKATKAN KENYAMANAN MUSHOLA DI DESA SUKAHARJA DENGAN KONSEP PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) - Prayogo Halim Subroto (JPMUJ, 2025)
The prayer room is a meeting place with the community, to complain about problems, war strategies, to decide on punishments, a place to learn besides the main place to pray the five daily prayers. There are prayer rooms that are crowded with worshipers, but there are also many prayer rooms that are abandoned by their congregations. Or, more subtly, many residents are less enthusiastic about praying in the prayer room. When seeing this disorder, what is felt is discomfort. This certainly interferes with concentration in performing worship. When this disorder turns into a habit, it can affect culture. The solution to overcome this disorder problem is to apply the concept of Clean and Healthy Living Behavior (PHBS). The prayer room in Sukaharja village has problems in terms of cleanliness. By applying the concept of Clean and Healthy Living Behavior, it is hoped that the cleanliness or sanctity of the prayer room will increase so that the congregation will be comfortable in the prayer room.